2018
DOI: 10.21037/tau.2018.03.17
|View full text |Cite
|
Sign up to set email alerts
|

Novel surgical techniques in female to male gender confirming surgery

Abstract: The current management of female to male (FTM) gender confirmation surgery is based on the advances in neo phalloplasty, perioperative care and the knowledge of the female genital anatomy, as well as the changes that occur to this anatomy with preoperative hormonal changes in transgender population. Reconstruction of the neophallus is one of the most difficult elements in surgical treatment of female transsexuals. While there is a variety of available surgical techniques, their results are not equally acceptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 23 publications
(27 reference statements)
0
38
0
Order By: Relevance
“…At present, the most commonly employed flap for phallic construction in transmasculine patients is the RFFF, first reported by Chang and Hwang [28] in 1984 [ Figure 2]. Advantages of the RFFF are: (1) extremely reliable vascular and peripheral neural anatomy [39] ; (2) the forearm is thin and pliable in most individuals, allowing for simultaneous creation of the pars pendulans urethra via the "tube-in-a-tube" technique [28,40] ; and (3) the RFFF having the highest innervation density of all the available flaps, providing the best potential for cutaneous reinnervation, and the ulnar, volar surface of the forearm being hair-free in many individuals, lessening or sometimes even obviating the need for hair removal prior to phalloplasty. In addition, the RFFF donor site results in no significant functional disturbance of the arm and hand for the large majority of patients [41] .…”
Section: Phalloplastymentioning
confidence: 99%
“…At present, the most commonly employed flap for phallic construction in transmasculine patients is the RFFF, first reported by Chang and Hwang [28] in 1984 [ Figure 2]. Advantages of the RFFF are: (1) extremely reliable vascular and peripheral neural anatomy [39] ; (2) the forearm is thin and pliable in most individuals, allowing for simultaneous creation of the pars pendulans urethra via the "tube-in-a-tube" technique [28,40] ; and (3) the RFFF having the highest innervation density of all the available flaps, providing the best potential for cutaneous reinnervation, and the ulnar, volar surface of the forearm being hair-free in many individuals, lessening or sometimes even obviating the need for hair removal prior to phalloplasty. In addition, the RFFF donor site results in no significant functional disturbance of the arm and hand for the large majority of patients [41] .…”
Section: Phalloplastymentioning
confidence: 99%
“…As described by Perovic, reconstruction with LDMF takes place in several stages including flap harvest and creation of the neophallus, two stages of urethroplasty using a buccal mucosa inlay, and finally the insertion of a penile prosthesis. Muscle sparing thoracodorsal artery perforator flaps have also been described in phalloplasty [41] , as well as other perforator flaps based on the subscapular vessel system including the scapular and parascapular flaps [3,42,43] .…”
Section: Ldmfmentioning
confidence: 99%
“…The latest modification of the original technique involves simultaneous removal of internal female organs, vaginectomy (colpocleisis), complete clitoral lengthening and straightening with the urethroplasty to the tip of the glans, and scrotoplasty with bilateral testicular implants insertion as a one-stage procedure. The current technique relies on the embryological and anatomical homology between the clitoris and penis, confirming the clitoris as a smaller version of the penis with impaired urethral development [2,14] [ Figure 1]. The procedure involves laparoscopically-assisted hysterectomy with bilateral salpingo-oophorectomy, if not performed prior to metoidioplasty, and complete vaginal mucosa removal by colpocleisis, with male-like perineoplasty, except for one small portion close to the native urethral meatus.…”
Section: Operative Techniquesmentioning
confidence: 99%
“…Minor complications are usually managed conservatively (hematoma, skin infection, urinary tract infection, partial skin necrosis, and dribbling and spraying during voiding). Major complications are usually related to urethroplasty and include either urethral fistulae or stricture, problems with testicular implants (displacement and rejection), and persistent vaginal cavity; these require surgical repair [2,5,26,33,34] . In our latest study, we reported overall complications in 46.8% of our 793 patients.…”
Section: Operative Techniquesmentioning
confidence: 99%
See 1 more Smart Citation